2002
DOI: 10.1152/ajpheart.00559.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear methods of biosignal analysis in assessing terbutaline-induced heart rate and blood pressure changes

Abstract: of biosignal analysis in assessing terbutaline-induced heart rate and blood pressure changes. Am J Physiol Heart Circ Physiol 282: H773-H781, 2002; 10.1152/ajpheart. 00559.2001.-The aim of this study was to characterize how different nonlinear methods characterize heart rate and blood pressure dynamics in healthy subjects at rest. The randomized, placebo-controlled crossover study with intravenous terbutaline was designed to induce four different stationary states of cardiovascular regulation system. The R-R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 29 publications
1
93
0
Order By: Relevance
“…Only four previous studies assessed ApEn in the context of BP. [18][19][20][21] In these studies, ApEn showed dependence on different states of cardiovascular regulation. ApEn calculation could easily be implemented in software packages accompanying devices for 24-h ABPM.…”
Section: Discussionmentioning
confidence: 86%
“…Only four previous studies assessed ApEn in the context of BP. [18][19][20][21] In these studies, ApEn showed dependence on different states of cardiovascular regulation. ApEn calculation could easily be implemented in software packages accompanying devices for 24-h ABPM.…”
Section: Discussionmentioning
confidence: 86%
“…The embedding dimension m (length of sequences to be compared) may range from 2 to 10 while the filter parameter r (tolerance for accepting matches) may range from 0.10 to 0.50. In the present investigation, m was fixed at two while the filter parameter r was set at 20% of the standard deviation of the time series, based on previous criteria (28).…”
Section: Ecg Signal Acquisitionmentioning
confidence: 99%
“…The mean of each RRI subepoch was calculated. Stationarity was calculated as the ratio of the SD of the subepoch means to the SD of the whole time series (28). A stationarity value near zero means the signal is stationary, and an increased value is reflective of increased nonstationarity.…”
Section: Ecg Signal Acquisitionmentioning
confidence: 99%
“…Many different methods for computing the complexity of time series have been defined and used successfully to analyze EEG data (Chen et al, 2009;Kuusela et al, 2002). Sample entropy, a measure of nonlinear time series complexity, was significantly higher in certain regions of the right hemisphere in pre-term neonates that received skin-to-skin contact than in those that did not, indicating faster brain maturation (Scher et al, 2009).…”
Section: Univariate Measuresmentioning
confidence: 99%